Hubungan Agama dan Negara dalam Konteks Modernisasi Politik di Era Reformasi - Masykuri Abdillah (Universitas Islam Negeri Jakarta, 2013)
Abstract: The Relationship of Religion and State within the Context of Political Modernisation in the Reform Era. Political modernization in Indonesia to some extent has brought about political secularization. Yet, in the Pancasila state, the process will not lead to a secular state. The relationship between religion and the state is an intersectional relationship, neither fully integrated nor completely separate. In the reform era, democratic political modernization has implications on the emergence of new political parties, including Islamic parties. On the other hand, the freedom of expression in certain cases has led to disputes and conflicts that can disrupt social harmony and national integration. In this context, religion can provide a positive contribution as an integrative factor that values social diversity, and not as a disintegrative factor that supports social exclusivism.Keywords: political modernization, secularization, religion and public policy, religion, religion and political participation, religion and national integrationAbstrak: Hubungan Agama dan Negara dalam Konteks Modernisasi Politik di Era Reformasi. Modernisasi politik di Indonesia dalam tingkat tertentu telah menimbulkan sekularisasi politik. Namun, di negara yang berideologi Pancasila ini, proses itu tidak akan mengarah kepada negara sekuler. Hubungan antara agama dan negara adalah hubungan persinggungan, tidak sepenuhnya terintegrasi dan tidak pula sepenuhnya terpisah. Di era reformasi ini, modernisasi politik yang demokratis beri mplikasi kepada munculnya partai-partai politik baru, termasuk partai-partai Islam. Di sisi lain, ekspresi kebebas an dalam kasus-kasus tertentu telah menimbulkan perselisihan dan konflik yang bisa mengganggu harmoni sosial dan integrasi bangsa. Dalam konteks inilah agama dapat memberikan kontribusi yang positif sebagai faktor integratif yang menghargai kem ajemukan masyarakat dan bukan sebagai faktor disintegratif yang mendukung eksklusifisme dalam masyarakat.Kata Kunci: modernisasi politik, sekularisasi, agama dan kebijakan publik, agama dan partisipasi politik, agama dan integrasi nasionalDOI: 10.15408/ajis.v13i2.937